KESIAPAN PENGADILAN AGAMA DALAM MENYELESAIKAN PERKARA EKONOMI SYARIAH - Yulkarnain Harahab (Fakultas Hukum Universitas Gadjah Mada, 2008)
Preparation of court is one of factors that influences effectiveness of Act. The aim of this research is to know about preparation of Religious Court in Special Region of Yogyakarta to settle syariah economic case that be mentioned in Act number 3 of 2006 about changing of act number 7 of 1989 about Religious Court. Based on this research, Religious Courts in Special Region of Yogyakarta are not ready to settle syariah economic case as mentioned in Act number 3 of 2006 yet. There are some obstacles that be faced Religious Court to do the authority, that is, first, there is not Code of Syariah Economic yet, second, uncapability of judges, and third, facilities are not enough.